Evaluation of adulteration in Lavandula angustifolia Mill. products using GC/MS combined with chemometric methods - Zahra Tarasoli; Hakim Faraji; Fateme Tajabadi; Mohsen Shabani; Hamidreza Shahbazi (Institue of Medicinal Plants, ACECR, 2021)
Background: The essential oil of Lavandula angustifolia Mill. (L. angustifolia), a species from the Lamiaceae family, possesses several biological activities; therefore it is used in some herbal medicines. The lack of studies into identifying the essential oil of L. angustifolia and its similar appearance to Nepeta menthoides Boiss. & Buhse (N. menthoides) as "Ustukhuddoos" in Iranian traditional medicine, have caused misuse and adulteration in the products. Objective: In this study, the chemical compositions of L. angustifolia and N. menthoides essential oils, and three commercial herbal medicines of L. angustifolia essential oil in Iranian markets were evaluated and investigated as adulteration with the help of GC/MS analysis and chemometric methods. Methods: The essential oils of L. angustifolia and N. menthoides, and commercial samples were extracted by different extraction methods. Furthermore, their chemical compositions were evaluated by GC/MS analysis. After identification of components by GC/MS, the obtained results were assessed by principal component analysis (PCA, Unscrambler X version 10.4) for clustering. Results: Results showed that all three commercial herbal preparations matched with the manufacturer's claim about using L. angustifolia essential oil in the products. PCA distinguished two groups which were characterized based on different types and amounts of the components. Conclusion: GC/MS analysis with the help of chemometric methods is a powerful method to evaluate and discriminate between the essential oils and their products. In general, the combination of instrumental analysis and clustering chemometric analysis can provide an accurate tool for identifying misuse between plant species.